Higher cerebrospinal fluid tau is associated with history of traumatic brain injury and reduced processing speed in Vietnam‐era veterans: A Department of Defense Alzheimer's Disease Neuroimaging Initiative (DOD‐ADNI) study. Issue 1 (14th October 2021) - Clark, Alexandra L.; Weigand, Alexandra J.; Bangen, Katherine J.; Thomas, Kelsey R.; Eglit, Graham M.L.; Bondi, Mark W.; Delano‐Wood, Lisa
Abstract: Introduction: Our goal was to determine whether cognitive and cerebrospinal fluid (CSF) markers of tau and amyloid beta 1‐42 (Aβ42 ) differ between Vietnam‐era veterans with and without history of traumatic brain injury (TBI) and whether TBI moderates the association between CSF markers and neurocognitive functioning. Methods: A total of 102 male participants (52 TBI, 50 military controls [MCs]; mean age = 68) were included. Levels of CSF Aβ42, tau phosphorylated at the threonine 181 position (p‐tau), and total tau (t‐tau) were quantified. Group differences in CSF markers and cognition as well as the moderating effect of TBI on CSF and cognition associations were explored. Results: Relative to MCs, the TBI group showed significantly higher p‐tau ( P = .01) and t‐tau ( P = .02), but no differences in amyloid ( P = .09). TBI history moderated the association between CSF tau and performance on a measure of processing speed (t‐tau: P = .04; p‐tau: P = .02). Discussion: Tau accumulation may represent a mechanism of dementia risk in older veterans with remote TBI.